MODEL PEMBERDAYAAN INDUSTRI KECIL MAKANAN MELALUI PENGEMBANGAN KEWIRAUSAHAAN DI KOTA MATARAM - SILFIA HERLINA; NI WAYAN PUTU MEIKAPASA; STEVANY HANALYNA DETHAN (Universitas Mahasaraswati Mataram, 2018)
This research is a descriptive study conducted on 30 small food industry entrepreneurs in the city of Mataram, with the aim of knowing the complexity of the problems faced by small food industry entrepreneurs and efforts to improve their empowerment. Data were analyzed using qualitative analysis.The complexity of the problems faced by small food industries in the city of Mataram are internal factors and external factors. The internal factors faced are: lack of capital and limited access to finance, quality of Human Resources (HR), technology, weak business networks and market penetration capabilities, mentality of SME entrepreneurs. From the external constraints, the business climate is not yet fully conducive, the limited business facilities and infrastructure and the nature of products with short durabilityTo develop its business, efforts to increase empowerment are needed, including a). Capital assistance is needed with the provision of subsidized credit, with easy and uncomplicated requirements, b). Creation of a conducive business climate, c). existence of business protection, d). partnership development is needed, e). business management training.In order that the small-scale food industry in Mataram City can be empowered and developed, it is recommended that the businessmen synergize with similar businesses and form a joint business group (KUB). In addition, it also improves managerial aspects, including: increasing productivity, increasing marketing capabilities, and developing human resources